2022
DOI: 10.1186/s12885-022-09176-1
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle albumin-bound paclitaxel and PD-1 inhibitor (sintilimab) combination therapy for soft tissue sarcoma: a retrospective study

Abstract: Background There is increasing evidence that combination therapy with nanoparticle albumin-bound paclitaxel (nab-paclitaxel) and programmed cell death protein 1 (PD-1) inhibitor is safe and efficacious in treating many types of malignant tumors. However, clinical data demonstrating the effect of this treatment combination for patients with metastatic soft tissue sarcoma (STS) are currently limited. Methods The clinical data of patients with metasta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…Sintilimab is a PD-1 inhibitor marketed in China ( Hoy, 2019 ). In our previous study, its safety and promising antitumor activity in STS were confirmed ( Tian et al, 2022 ). Recent clinical trials have shown that sintilimab combined with chemotherapy is more effective than chemotherapy alone in advanced esophageal, gastric, and lung cancers ( Yang et al, 2021 ; Zhou et al, 2021 ; Jiang et al, 2022 ; Lu et al, 2022 ).…”
Section: Introductionmentioning
confidence: 75%
“…Sintilimab is a PD-1 inhibitor marketed in China ( Hoy, 2019 ). In our previous study, its safety and promising antitumor activity in STS were confirmed ( Tian et al, 2022 ). Recent clinical trials have shown that sintilimab combined with chemotherapy is more effective than chemotherapy alone in advanced esophageal, gastric, and lung cancers ( Yang et al, 2021 ; Zhou et al, 2021 ; Jiang et al, 2022 ; Lu et al, 2022 ).…”
Section: Introductionmentioning
confidence: 75%
“…There was no association between treatment efficacy and PD-L1 expression but combined treatment (pembrolizumab plus chemotherapy or pembrolizumab plus targeted therapy) could increase the risk for developing severe adverse events. Similarly, in a retrospective study of 28 patients with metastatic STS including angiosarcoma, UPS, epithelioid sarcomas, fibrosarcoma, synovial sarcomas, leiomyosarcomas, pleomorphic liposarcoma, and rhabdomyosarcoma, the nanoparticle albumin-bound paclitaxel was combined with sintilimab in patients with metastatic STS (Tian Z et al in January 2022) (57). The results showed modest activity and fairly tolerable toxicity with no grade 4 adverse events.…”
Section: Combinations Of Immune Checkpoint Inhibitors With Chemotherapymentioning
confidence: 97%
“…Firstly, cancer nanomedicines can be utilized to deliver cytotoxic chemotherapy agents capable of inducing the release of tumor antigens and eliciting immunogenic cell death (step 1, Figure 3 ). The clinical potential of combining Abraxane ® with the PD-1 inhibitor atezolizumab has already been demonstrated in a phase 3 clinical trial for the treatment of triple negative breast cancer and in a retrospective study of soft tissue sarcoma, with angiosarcoma patients reporting a significantly prolonged free survival compared to other subtypes 224 . Doxil ® , similarly to Abraxane ® , induces immunogenic cell death by promoting immune cell infiltration and reverting tumor immunosuppression 225 .…”
Section: Strategies To Overcome Barriers To Sarcoma Immunotherapymentioning
confidence: 99%